Understanding The Interactions Between Plants and Pathogenic Microorganisms and Their Impact on Plant Health and Productivity - Muneeba; Faran Muhammad; Muhammad Shafique; Muhammad Dilawaiz Khan (Indus Journal of Bioscience Research, 2023)
Background: As living organisms, plants are continuously exposed to a variety of microorganisms, such as bacteria, fungi, viruses, and nematodes, some of which can cause diseases and inhibit plant growth.Objectives: This study aimed to investigate the interactions between plants and pathogenic microorganisms and assess their influence on plant health and productivity.  Methods: A series of experiments were conducted to evaluate disease severity, gene expression, yield reduction, and disease incidence in different plant species infected with specific pathogens.Results: The results revealed a significant mean disease severity rating of 2.3 for Tomato infected with Xanthomonas campestris and 3.6 for Tomato infected with Fusarium oxysporum. Additionally, gene expression analysis showed a fold change of 2.5 for PR1a in Tomato infected with X. campestris, indicating a significant upregulation. Wheat infected with Puccinia graminis exhibited a mean disease severity rating of 4.6, while F. graminearum resulted in a mean rating of 3.1. Yield reduction was observed in Maize infected with F. graminearum, with a decrease from 5000 kg/ha in the control to 3800 kg/ha in the infected condition, corresponding to a 24.0% reduction. Similarly, Rice infected with Magnaporthe oryzae experienced a yield reduction of 20.0%, with the infected yield dropping from 6500 kg/ha to 5200 kg/ha. Disease incidence was significantly higher in Apple infected with Venturia inaequalis, with a mean incidence of 12.5%, and Tomato infected with Alternaria solani, with a mean incidence of 21.4%, compared to the control groups.Conclusion: These findings underscore the importance of understanding plant-pathogen interactions for effective disease management and the development of strategies to enhance agricultural productivity.